2016
DOI: 10.4047/jap.2016.8.5.396
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized clinical trial of hydrophilic tapered implant placement at maxillary posterior area: 6 weeks and 12 weeks loading

Abstract: PURPOSEEarly loading of implant can be determined by excellent primary stability and characteristic of implant surface. The implant system with recently improved surface can have load application 4-6 weeks after installing in maxilla and mandible. This study evaluated the effect of healing period to the stability of hydrophilic tapered-type implant at maxillary posterior area.MATERIALS AND METHODSThis study included 30 patients treated by hydrophilic tapered-type implants (total 41 implants at maxilla) and cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…The patients also took periapical radiographs after final restoration, 6 and 12 months after restoration and final follow up period. The authors concluded that the period of 6 weeks can make the similar clinical prognosis of implants to that of healing period of 12 weeks and after 12 months all implants survived and the success rate was 97.56% (24).…”
Section: Discussionmentioning
confidence: 96%
“…The patients also took periapical radiographs after final restoration, 6 and 12 months after restoration and final follow up period. The authors concluded that the period of 6 weeks can make the similar clinical prognosis of implants to that of healing period of 12 weeks and after 12 months all implants survived and the success rate was 97.56% (24).…”
Section: Discussionmentioning
confidence: 96%
“…The results of this study are in agreement with one-year follow-up studies on implants placed in the maxillary posterior region using an early loading protocol. Kim et al 35 reported a 97.0% one-year implant success rate in the maxillary posterior area after a 3-month loading period. Kim et al 36 also indicated a one-year success rate of 97.56% by applying a loading protocol between 6 and 12 weeks to an implant placed in the posterior edentulous part of the maxilla.…”
Section: Discussionmentioning
confidence: 99%
“…Elkhaweldi et al reported that the survival rate of RBM surfacetreated implants was 95.2%, but the survival rate of SLA surface-treated implants was higher than 99.1% [10]. Using this SLA surface treatment method, Osstem (Busan, Korea) developed implants with SA surfaces that were subjected to sandblasting and acid etching using alumina, but more long-term observational studies on the implants are necessary [11][12][13].…”
Section: Discussionmentioning
confidence: 99%